Peningkatan Kreativitas Anak Melalui Media Smart Box - Aini Sapitri; fauziddin; Lusi Maleni (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This research aims to increase children's creativity through smart box media at Adzkyah Bangkinang Kindergarten, Kampar Regency. This research was motivated by the low creativity abilities of children in games. The type of research used was classroom action research, in this case the research subjects were children aged 4-5 years. Meanwhile, the object of this research is a smart box media game. This research was carried out in 2 cycles, each cycle held 2 meetings. The data collection techniques used in this research are observation, interviews and documentation. Based on the results of the research, before the action, 2 children or 13.3% of their creativity had developed according to expectations, 6 children or 40% of their creativity had begun to develop, and 7 children or 46.6% of their creativity had not yet developed. In cycle I there was an increase in creative abilities, 2 children or 13.3% of children's creativity developed according to expectations, 9 children or 60% of children's creativity began to develop, and 4 children or 26.7% of children's creativity had not yet developed. Meanwhile, in cycle II children's creative abilities increased, 2 children or 13.5% of children's creativity developed very well, 8 children or 55.2% of children's creativity developed as expected, and 5 children or 33.4% of children's creativity began to develop. Thus, it can be concluded that the use of smart box media can increase the creative abilities of children at the Adzkyah Bangkinang Kindergarten, Kampar Regency.